Fast neutron spectroscopy with Mimac-FastN : a mobile and directional fast neutron spectrometer, from 1 MeV up to 15 MeV. (April 2020) - Sauzet, N; Santos, D; Guillaudin, O; Bosson, G; Bouvier, J; Descombes, T; Marton, M; Muraz, JF
Abstract: In the frame of direct dark matter search, the fast neutrons producing elastic collisions are the ultimate background. The MIMAC (MIcro-tpc MAtrix Chambers) project has developed a directional detector providing the directional signature to discriminate them based on 3D nuclear tracks reconstruction. The MIMAC team of the LPSC has adapted one MIMAC chamber as a portable fast neutron spectrometer, the Mimac-FastN detector, having a very large neutron energy range (10 keV - 200 MeV) with different gas mixtures and pressures. The present paper shows its main features and functionality and demonstrates its potential in the energy range from 1 MeV to 15 MeV.